ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEUNGGULAN KOMPARATIF DAN KEUNGGULAN KOMPETITIF PADA UKM PENGRAJIN BATU MARMER DI KABUPATEN TULUNGAGUNG - Nu Graha, Andi (Jurnal Ekonomi Modernisasi, 2010)
Marketing Global was viewed that could give basically of business performance. It had been controlled and measured. Whereas certain business do not have attention toward global market. The development of middle and small industries face regional market and global market have to base with strongest effort and continuity. Hence, the production of middle and small business has comparative advantagesÂ  competitive advantages. The purpose of this research is to know the various factors both comparative and competitive advantages in middle and small businesess of Marble Stones in Tuluagung Region, East Java. The analysis research are found : (1) The main problem of comparative advantages in middle and small businesess was the lower of wages labor, (2) the largest of scope area, (3) the aglomeration area and the government policies. The result of this research are production factors, the similar industries and the industries supported.